Lactobacillus casei reduces the extracellular matrix components of fluconazole-susceptible Candida albicans biofilms - Panariello, Beatriz H. D. [UNESP]; Klein, Marlise Inez [UNESP]; Dias, Luana Mendonça [UNESP]; Bellini, Amanda [UNESP]; Costa, Vitoria Bonan [UNESP]; Barbugli, Paula Aboud [UNESP]; Pavarina, Ana Claudia [UNESP] (Taylor & Francis, 2021)
Fluconazole-sensitive (CaS) and -resistant (CaR) C. albicans were grown as single-species and dual-species biofilms with Lactobacillus casei (Lc) and Lactobacillus rhamnosus (Lr). Single-species Lc and Lr were also evaluated. Biofilm analysis included viable plate counts, the extracellular matrix components, biomass, and structural organization. Lc reduced the viability of CaS, water-soluble polysaccharides, and eDNA in CaS + Lc biofilm. Lc biofilm presented more eDNA than CaS. The total biomass of CaS + Lc biofilm was higher than the single-species biofilms. The viability of Lc and Lr was reduced by CaR dual-species biofilms. The total and insoluble biomass in CaS + Lr was higher than in single-species CaS biofilms. Lc hindered the growth of CaS, and their association hampered matrix components linked to the structural integrity of the biofilm. These findings allow understanding of how the implementation of probiotics influences the growth of C. albicans biofilms and thereby helps with the development of novel approaches to control these biofilms.
Keywords: biofilm extracellular matrix; Candida albicans; Lactobacillus casei; Lactobacillus rhamnosus